The influence of the availability of human resources, facilities and infrastructure on organizational work effectiveness at the Faculty of Social and Political Sciences Nusa Cendana University - H Seran, Yani; Seran, Marisa S.B. (Indonesia Auditing Research Journal, 2024)
This research raises the problem of how to increase the effectiveness of organizational work by improving the availability of human resources, facilities and infrastructure at the Faculty of Social and Political Sciences, Nusa Cendana University. With the aim of finding out how much influence the availability of human resources, facilities and infrastructure has on the effectiveness of organizational work at the Faculty of Social and Political Sciences, Nusa Cendana University. The data analysis used in this research is a simple correlation analysis which shows that there is a simple relationship between the provision of human resources, facilities and infrastructure and the effectiveness of organizational work at the Faculty of Social and Political Sciences, Nusa Cendana University. After knowing the correlation between each variable, the next analysis is regression analysis. This analysis is intended to determine whether the influence of the identified factors (Xi) included in this research has an effect on the effectiveness of organizational work at the Faculty of Social and Political Sciences, Nusa Cendana University. The results of the research show that there is an influence between the provision of human resources, facilities and infrastructure on the effectiveness of organizational work at the Faculty of Social and Political Sciences, Nusa Cendana University. These three variables must be improved in both quality and quantity so that the effectiveness of organizational work at the Faculty of Social and Political Sciences, Nusa Cendana University can be further improved